Impact of storage techniques on ovine temporomandibular joint discs composition and physicochemical properties - Trindade, Daniela; Calado, Cecília R. C.; Silva, João C.; Maurício, Ana C.; Alves, Nuno; Moura, Carla (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe temporomandibular joint disc plays a vital role in daily activities, and when it is compromised, it significantly impairs oral health and quality of life. The use of animal tissues for decellularized tissue engineering applications has been gaining interest, and an appropriate method for storing these tissues before processing has yet to be explored.MethodsThis study characterizes the native temporomandibular ovine disc and compares storage protocols aimed at maintaining its morphology, biochemical content, and mechanical and thermal properties. Three storage protocols were tested: (i) freezing at −20 °C in phosphate-buffered saline (PBS) and thawing at 4 °C (PBS + 4 °C); (ii) freezing at −20 °C in PBS and thawing at room temperature (RT) (PBS + RT); and (iii) wrapping the discs in PBS-embedded gauze, freezing at −20 °C, and thawing at RT (Gauze + RT). Protocols were evaluated for short-term storage at 1, 7, and 14 days, and compared with a native and a collagenase-treated disc.ResultsAll conservation protocols induced changes, though less pronounced than the enzymatic degradation. The PBS + 4 °C and PBS + RT highlighted contrasting biochemical and mechanical outcomes, and thermal analysis revealed alterations to collagen structure. The Gauze + RT protocol preserved the biochemical content over time but exhibited a higher compression modulus on day 14.ConclusionThese results highlight how crucial it is to select adequate conservation techniques when preparing the TMJ disc for future studies.